2021
DOI: 10.1016/j.tvjl.2021.105661
|View full text |Cite
|
Sign up to set email alerts
|

Role of paraoxonase-1 as a diagnostic marker for feline infectious peritonitis

Abstract: Feline infectious peritonitis (FIP) is characterized by a huge inflammatory response accompanied by oxidative stress. Paraoxonase-1 (PON-1) is a liver enzyme that circulates in blood bound to high density lipoproteins. Its hydrolytic properties have been associated with an antioxidant activity and its role as negative acute phase reactant has been investigated in people and animals. A paraoxon based method has been validated to measure feline serum PON-1 activity, allowing to observe a negative correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Significantly lower PON‐1 activity was observed in cats with FIP compared with healthy cats; moreover, cats with effusive forms showed significantly lower PON‐1 and higher SAA concentrations compared with cats with noneffusive forms 109 . PON‐1 activity can accurately discriminate cats with FIP from cats without FIP, but with similar clinical presentations 110 . A threshold of 78.30 U/L yielded a sensitivity of 100% and a specificity of 50.4%, while a threshold of 24.90 U/L maximized specificity (94.4%) and had a sensitivity of 44.1%, making PON‐1 activity a good confirmatory test for FIP 110 …”
Section: Future Perspectivesmentioning
confidence: 95%
See 1 more Smart Citation
“…Significantly lower PON‐1 activity was observed in cats with FIP compared with healthy cats; moreover, cats with effusive forms showed significantly lower PON‐1 and higher SAA concentrations compared with cats with noneffusive forms 109 . PON‐1 activity can accurately discriminate cats with FIP from cats without FIP, but with similar clinical presentations 110 . A threshold of 78.30 U/L yielded a sensitivity of 100% and a specificity of 50.4%, while a threshold of 24.90 U/L maximized specificity (94.4%) and had a sensitivity of 44.1%, making PON‐1 activity a good confirmatory test for FIP 110 …”
Section: Future Perspectivesmentioning
confidence: 95%
“…PON‐1 activity can accurately discriminate cats with FIP from cats without FIP, but with similar clinical presentations 110 . A threshold of 78.30 U/L yielded a sensitivity of 100% and a specificity of 50.4%, while a threshold of 24.90 U/L maximized specificity (94.4%) and had a sensitivity of 44.1%, making PON‐1 activity a good confirmatory test for FIP 110 …”
Section: Future Perspectivesmentioning
confidence: 99%
“…On the other hand, the prevalence of coronary artery diseases such as atherosclerosis and their mortality is increasing globally (26,31). Therefore, finding compounds that can increase the activity of this enzyme will be very effective in preventing atherosclerosis (9). The result of the current study showed that the combination of felodipine and enalapril in the treatment of essential hypertension with coronary artery disease can significantly enhance PON1 gene expression in the study group in comparison with the control group.…”
Section: Comparison Of Adverse Reactionsmentioning
confidence: 59%
“…Although all paraoxonases can hydrolyze longchain aromatic and aliphatic lactones, PON-1 has arylesterase activity, too. There is ample evidence that PON-1 may have a protective effect on atherogenesis (9). PON-1 seems to be the main factor in the antiinflammatory function of HDL by preventing LDL oxidation.…”
Section: Comparison Of Adverse Reactionsmentioning
confidence: 99%
See 1 more Smart Citation